Amplitude-integrated electroencephalography and MRI findings in a case of severe neonatal methicillin-resistant Staphylococcus aureus meningitis. (21st December 2010) - Olischar, Monika; Hunt, Rod W; Daley, Andrew J; Clifford, Vanessa; Tingay, David G
Abstract : Methicillin-resistant Staphylococcus aureus (MRSA) can cause serious infection among hospitalised patients. The emergence of community acquired strains of MRSA (CA-MRSA) increases the potential exposure of newborns. The high incidence of reported meningitis in neonates in large CA-MRSA outbreaks suggests increased virulence in the neonatal population. The authors describe a case of severe meningitis due to MRSA in a previously healthy neonate and include findings from amplitude-integrated electroencephalography (aEEG) and MRI.